A Critical Review of Blockchain Consensus Model - Khan, D. (Institute of Electrical and Electronics Engineers Inc., 2020)
The state-of-art Blockchain technology has been receiving enormous attention from researchers and industry practitioners in recent years. Basically Blockchain is a distributed immutable ledgerutilized by user mainly to perform transactions across various nodes in a blockchain network after a mutual consensus of all the associated nodes in the network. Noticeably, Blockchain is made famous by the Bitcoin cryptocurrency. As of 2017 Blockchain has seen to disrupt many applications to a global worth of 150B. The consensus models are responsible for the process of reaching an agreement between all nodes in blockchain to accept a new block. The consensus model plays a vital role in sustaining Blockchain efficiency. Using the right consensus model can significantly increase the performance of blockchain operation. The consensus models can be divided into two categories. The first category is the proof-based consensus model whereby a node in the Blockchain performs enough proof over other nodes to gain a chance to append the next block to the chain. The second category is the voting-based model in which nodes need to share their results in verifying a transaction of a new block before a final decision is reached. In this paper we discuss the characteristics of some major existing consensus models and provide some critical reviews on their performances. The reviewis mainly concerning these aspects: transaction throughput, latency, network bandwidth, and storage. Â© 2020 IEEE.